The theoretical framework on humanist ethno-metaphorical mathematics learning model: An impactful insight in learning mathematics - Hendriana, Heris; Prahmana, Rully Charitas Indra; Ristiana, Muhammad Ghiyats; Rohaeti, Euis Eti; Hidayat, Wahyu (Frontiers in Education, 2022)
The educational revolution has posed an immense challenge to the world of education. It demands the development of a generation that can take on the challenges and changes bred by the ever-rapid revolution. Thus, education must inevitably enable improvements in individual hard and soft skills required to keep up with such changes, including hard mathematical and soft skills. The problem is that not all mathematics learning approaches, particularly in the case of Indonesia, are capable of such improvements and of answering such demands, challenges, and changes posed by the revolution. Therefore, the critical objective of this study is to design and construct the theoretical framework by using an integrative literature review with systematic analysis based on various relevant pieces of literature that fit the theoretical framework under development. In this study, a theoretical framework for Humanist Ethno-Metaphorical Mathematics Learning is designed and constructed as a theoretical foundation. This theory is designed for creating a humanist mathematics learning approach based on ethnomathematics and metaphorical thinking to develop students’ mathematical hard skills and soft skills and thus enable them to deal with current and future problems and changes.